Governance and Protection of Indonesian Migrant Workers in Malaysia - Prianto, Andi Luhur; Amri, Aqmal Reza; Ajis, Mohd Na’eim (University of Jember, 2023)
Protecting Indonesian migrant workers (IMWs) in Malaysia is a matter of great significance due to Indonesia's status as one of the primary source countries for migrant workers to Malaysia. Consequently, it necessitates the implementation of comprehensive governance measures by both nations. This paper aims to analyze the joint endeavors and collaborative frameworks established between governments of Indonesia and Malaysia. Additionally, it seeks to identify the network of policies and innovations enacted in both countries related to the protection and regulation of migrant workers. This research was enhanced through the utilization of NVivo qualitative analysis software. This article shows that efforts to protect IMWs in Malaysia involve many government institutions in both countries, especially at ministerial and departmental levels. The policies established between the two countries are also able to support the success of migrant protection, especially with the agreement between the two countries in the form of signing a Memorandum of Understanding (MoU). This MoU gave birth to innovation in digital-based migrant worker protection services, namely a